2018
DOI: 10.1111/are.13686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grapeVitis viniferaseed oil supplementation on growth, survival, fatty acid profiles, antioxidant contents and blood parameters in rainbow troutOncorhynchus mykiss

Abstract: In this study, effects of grape Vitis vinifera seed oil supplementation (0, 250 mg, 500 mg, 1,000 mg/kg feed) for 60 days on rainbow trout Oncorhynchus mykiss juveniles were investigated. The average final fish weights were not different between the control group and 500 mg/kg feed group (p > .05), but 250 mg/kg feed group were lower than those of the control group, and 1,000 mg/kg feed group were higher than those of the control group. Although the SFA, MUFA and n3 ratios of the control group were higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 56 publications
8
31
0
Order By: Relevance
“…Aquaculture represents an interesting field of investigation, providing itself as a source for alternative food production. Recently, a study tested the effect of grape oil supplementation towards the growth performance (including fatty acid content, enzyme activity and blood biochemistry) of rainbow trout (Arslan et al ., ). It emerged that this supplement (1000 mg kg −1 ) positively affected the growth performance.…”
Section: Applicationsmentioning
confidence: 97%
“…Aquaculture represents an interesting field of investigation, providing itself as a source for alternative food production. Recently, a study tested the effect of grape oil supplementation towards the growth performance (including fatty acid content, enzyme activity and blood biochemistry) of rainbow trout (Arslan et al ., ). It emerged that this supplement (1000 mg kg −1 ) positively affected the growth performance.…”
Section: Applicationsmentioning
confidence: 97%
“…The current study revealed improved growth performance in fish fed GSE. In parallel, the positive effects of dietary GSE and grape seed oil in tilapia (Oreochromis niloticus) and rainbow trout were observed (Arslan et al, 2018;Zhai et al, 2014). The presence of polyphenolic compounds in diet might protect the intestinal mucosa against different pathogens and oxidative damage, thereby leading to better absorption of nutrients (Abu Hafsa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fish growth performance and immune responses can be induced by several materials such a plant extract. The grape seed extract contains several bioactive substances such as vitamins C and E, and fatty acids that can stimulate the immune system by the production of bioactive molecules (immunoglobulin, lysozyme, complement,) and increasing the activity of phagocytosis (Arslan et al, 2018;Gokoglu et al, 2008;Kao et al, 2010;Lange et al, 2014). Hence, the medicinal utilization of grape seed extract (GSE) is due to the presence of the mentioned bioactive compounds, which can also affect fish growth and immunity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations